An expedient synthesis of highly functionalized 1, 3-dienes by employing cyclopropenes as C4 units. Issue 46 (13th May 2021) - Jiang, Chengzhou; Wu, Jiamin; Han, Jiabin; Chen, Kai; Qian, Yang; Zhang, Zhengyu; Jiang, Yaojia
Abstract : An efficient method has been described to synthesize 1, 3-dienes by cleaving the CC bond of enaminones with cyclopropenes under very mild reaction conditions, including low rhodium catalyst-loading, ambient temperature, and a neutral solvent system. Abstract : An efficient method has been described to synthesize dicarbonyl functionalized 1, 3-dienes by cleaving the CC bond of enaminones with cyclopropenes in the presence of a rhodium catalyst. The acetate-substituted cyclopropenes are judiciously chosen as standard C 4 units of 1, 3-diene precursors. The reactions are believed to undergo a unique cutting and insertion process, involving a CC bond cleavage of the enaminone and insertion of a new C (sp 2 ) source with the formation of two C–C single bonds. A broad range of substrates can be used to synthesize the corresponding 1, 3-dienes under very mild reaction conditions, including low catalyst-loading, ambient temperature, and a neutral reaction solvent.